The EGF receptor family : biologic mechanisms and role in cancer - Carpenter, Graham (Elsevier Academic Press, 2004)
The enormity of the literature on growth factors, plus the breadth of the biological disciplines and technical expertise required prohibits a comprehensive review by even a multi-disciplinary panel of authors. To provide an alternative that is feasible for authors and digestible by readers, this review compendium consists of a collection of articles, each covering an aspect of the ErbB/EGF field. This compilation features articles on growth factor ligands, neuregulins, and individual receptors. The second part of the book concentrates on the biological context of the ErbB receptors, particularly in mammary development and in cancer. It concludes with a discussion of the genetic systems that have enabled significant advances in research in this area.